Effect of Ascorbic Acid on Aceclofenac Induced Gastric Mucosal Damage: Role of Antioxidant Enzymes and Lipid Profile - Darbar, S.; Bose, A.; Chatterjee, N.; Roy, B.; Mandal, U.; Veeran Gowda, K.; Ghosh, A.; Pal, T.K. (Asian Journal of Chemistry, 2010)
The present work has been undertaken to study the effect of ascorbic acid, a potent antioxidant on experimental gastric ulceration induced by aceclofenac and their possible antioxidative mechanism to cure ulcer. Gastric mucosal damage was produced in rats by administering aceclofenac (90 mg/ kg/d) orally. Preadministration of ascorbic acid (200 mg/kg/d) as a food supplement, decreased the ulcer index, lipid peroxidation, conjugated diene and protein carbonyl content and increased the antioxidant enzyme levels. The lipid levels were maintained at near normalcy when treated with ascorbic acid in aceclofenac-administered rats. The major mechanism involved appears due to free radical scavenging action and changes in lipid profile.